Educational Broadcast Model on Suara Edukasi Kulon Progo Community Radio during the Covid-19 Pandemic - Hermawan, Agung; Arifianto , Budi (Universitas Muhammadiyah Yogyakarta, 2022)
The existence of the Covid-19 pandemic has resulted in the learning process in most educational institutions being hampered. The issue of education, especially in Kulon Progo during the pandemic, is increasingly complicated, considering that some areas of this district are topography is mountainous. This makes internet signals difficult to get in some areas that are blank spots. To solve this problem, a community radio called Radio Suara Edukasi Kulon Progo was established at the Muhammadiyah Penggung Elementary School (SD), Kokap District, Kulon Progo Regency. This research aims to find out how to develop a community radio broadcast program model as a distance learning medium during the pandemic in Kulon Progo and to find out how to manage radio programs with analog transmitters in the digital era. This research uses positivistic paradigms with a qualitative descriptive approach. By obtaining sources from interviews, documents and direct observations. This research is an initiation of the problems contained from masduki research (2013) entitled Development and Problems of Community Radio in Indonesia. The results of this study found that this broadcast was carried out using the Azura Cast application. Broadcasting is done with streaming and the help of applications that allow them to collaborate to fill broadcast content anywhere.